Ekstrak Daun Meniran (Phyllanthus niruri L.) : Bagaimana Pengaruhnya Terhadap Jumlah Trombosit di Dalam Darah? - Sumiati, Risma Laila; Baehaki, Farhan; Nurdin, Nurdin; Pakpahan, Suyarta Efrida (Stannum : Jurnal Sains dan Terapan Kimia, 2024)
Thrombocytopenia is a condition in which the platelet count is below normal (<150,000-450,000 cells/mm3). Until now, the treatment of thrombocytopenia has not yet found a specific drug and there are side effects from chemical treatment, so alternative solutions are needed, one of which is the use of meniran leaves (Phyllanthus niruri L.). The meniran plant is a wild plant that is often found in the wild, on the streets, as well as vacant land so that people can easily get these plants. The aim of this research was to determine the effect of meniran leaf extract (Phyllanthus niruri L.) on the number of platelets in mice induced by sodium phenytoin. The method used in this research was True Experimental with Pretest and Posttest with Control Group Design consisting of 5 groups which aimed to determine the effect of meniran leaf extract on platelet counts. The data collection technique used in this study used primary data, which was obtained from the results of examining platelet counts on day 0, day 3 after induction and day 7 after treatment with meniran leaf extract (Phyllanthus niruri L.). Then the data obtained was tested using SPSS with the non-parametric Kruskal-Wallis and Mann-Whitney tests. From 25 experimental animals, the results showed that there was a relatively significant increase in the number of platelets after being given therapy with meniran leaf extract (Phyllanthus niruri L.) but there was no difference between each dose. Based on the research results, it can be concluded that meniran leaf extract (Phyllanthus niruri L.) has an effect on increasing the number of platelets.